Strategy for Mitigating Landslide Disaster Risk through Improving the Status of Disaster Resilient Villages (DESTANA) Case Study in Kemuning Village, Ngargoyoso District, Karanganyar Regency - Pipit Wijayanti; Rita Noviani; Anton Sabarno; Fajar Dwi Prasetya; Hafidz Habibulloh; Muhammad Ikyu Arqie Ramadhan; Nur Fadillah; Panca Rizky Ayu Ramadhany; Pundung Setia Lesana; Putri Mariamulia Utami; Riksa Histhika; Rochadi Setyo Wibowo; Siti Setiyowati (Universitas Sebelas Maret, 2020)
Kemuning Village is one of the areas with the highest potential for landslides in Ngargoyoso District, Karanganyar Regency. This service activity aims to help institutional strengthening of the Tangguh Disaster Village (Destana) in disaster planning at the village level in the context of increasing preparedness and disaster management of landslides. The activity was carried out in Kemuning Village with an implementation time of 1 month The research method through open interviews, field observations, document review, and then analyzed descriptively qualitatively. The results of the disaster resilience assessment indicate that Kemuning Village is included in the category of Main Disaster Resilient Village. Based on the assessment analysis presents indicators of disaster management systems, disaster risk management, quality and basic access in the village is still lacking so it needs to be improved. The target of service outcomes obtained from this activity is to optimize the role of disaster resilient villages to reduce the risk of landslide disasters.